ADVOCATING THE IMPORTANCE OF MALAY FARMERS’ AND FISHERMEN’S ASTRONOMICAL KNOWLEDGE AGAINST THE LIGHT POLLUTION OF MEGA-CONSTELLATION SATELLITES THROUGH HERITAGE DIPLOMACY - Majid, Marina Abdul (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2025)
Farmers and fishermen in Malaysia traditionally rely on their astronomical knowledge to signify seasons for paddy planting, navigation and choices of fish caught. This knowledge, though, has eroded over time. The installation of mega-constellation satellites by overseas companies brightens the night sky, preventing farmers and fishermen from detecting the stars to guide them. This study’s main objective emphasises the relevance of heritage diplomacy in advocating the importance of Malay farmers’ and fishermen’s astronomical knowledge through relevant initiatives by international and regional organisations to ensure that this legacy lives on for future generations. This is a qualitative study with a socio-legal approach. A textual analysis using interpretivism to interpret provisions among relevant international agreements and reference to non-binding documents that can protect astronomical knowledge and include the participation of farmers and fishermen was conducted. Secondary sources and visits to social media websites and blogs were also conducted and analysed through a content analysis. The result shows that Malaysia can use its foreign embassies to canvas for support for Articles 2 (1), 2 (2) and 2 (3) in the Convention for the Safeguarding of the Intangible Cultural Heritage, Articles 9.1 and 9.2 of the International Treaty of Plant and Genetic Resources, Paragraphs 9.4.2, 10. 2.1 and 12.12 of the Code of Conduct for Responsible Fisheries, the United Nations Educational, Scientific and Cultural Organization’s Astronomy and World Heritage Initiative, and the Food and Agriculture Organization’s Globally Important Heritage Systems. These relevant articles should be consulted by the United Nations Committee on the Peaceful Uses of Outer Space (UNCOPUOS) so they do not duplicate other initiatives. Malaysia should also advocate for an international agreement or guideline at the UNCOPUOS to control light pollution emanating from mega-constellation satellites. A display board showing Malaysian fishermen’s knowledge of stars at Tanjung Balau Museum in Johor preserves this heritage. Efforts to ensure the continuity of astronomical knowledge for future generations have included briefing and stargazing trips at the paddy and archaeological museums in Kedah, including the Malay cultural significance of stars showing times for paddy planting and the monsoon season, which prevents fishing in Peninsular Malaysia.